Physiological and Behavioral Responses of Dairy Cattle to the Introduction of Robot Scrapers - Doerfler, Renate L.; Lehermeier, Christina; Kliem, Heike; Möstl, Erich; Bernhardt, Heinz (Frontiers in Veterinary Science, 2016)
Autonomous mobile robot scrapers are increasingly used in order to clean the floors on dairy farms. Given the complexity of robot scraper operation, stress may occur in cows due to unpredictability and lack of control of the situation. Experiencing stress can impair animal welfare and in the long-term the health and milk production of the cows. Therefore, this study addressed potential stress responses of dairy cattle to the robot scraper after introducing the autonomous mobile machine. 36 cows in total were studied on three different farms to explore possible modifications in cardiac function, behavior, and adrenocortical activity. The research protocol on each farm consisted of four experimental periods including one baseline measurement without robot scraper operation followed by three test measurements, in which cows interacted with the robotic cleaning system. Interbeat intervals were recorded in order to calculate the heart rate variability parameter RMSSD, behavior was observed to determine time budgets, and fecal samples were collected for analysis of the cortisol metabolites concentration. A statistical analysis was carried out using linear mixed-effects models. Heart rate variability decline immediately after the introduction of the robot scraper and modified behavior in the subsequent experimental periods indicated a stress response. The cortisol metabolites concentration remained constant. It is hypothesized that after the initial phase of decrease, heart rate variability stabilized through the behavioral adjustments of the cows in the second part of the study. Persistent alterations in behavior gave rise to the assumption that the animals’ habituation process to the robot scraper was not yet completed. In summary, the present study illustrated that the cows showed minor signs of disturbance towards the robotic cleaning system. Thus, our findings suggest that dairy cattle can largely adjust their behavior to avoid aversive effects on animal welfare. Additional research can provide further insight into the development of the animal-machine interaction beyond the initial phase of robot scraper operation considered in this study.